Neurosteroids Involvement in the Epigenetic Control of Memory Formation and Storage - Colciago, Alessandra (Neural Plast, 2016)
Memory is our ability to store and remember past experiences; it is the result of changes in neuronal circuits of specific brain areas as the hippocampus. During memory formation, neurons integrate their functions and increase the strength of their connections, so that synaptic plasticity is improved and consolidated. All these processes recruit several proteins at the synapses, whose expression is highly regulated by DNA methylation and histone tails posttranslational modifications. Steroids are known to influence memory process, and, among them, neurosteroids are implicated in neurodegenerative disease related to memory loss and cognitive impairment. The epigenetic control of neurosteroids involvement in memory formation and maintenance could represent the basis for neuroregenerative therapies.